Manajemen Profitabilitas Economic Value Added pada Bank - Setiadi, Pompong Budi (Jurnal Aplikasi Manajemen, 2014)
The aims of this study are to examine the theoretical basis and provide a complete picture on the profitability of the Bank through Economic Value Added (EVA). The method used in this study was the study of literature or theoretical studies. The results of this study concluded that (1) Economic Value Added is a measure of financial performance that are relevant due to the measurement based on value added, EVA is a measure of economic value added that is generated by the company as a result of management activities. (2) With the EVA, the owner of the bank is only going to give a reward (reward) on activities that add value and discard the activities in which destroy or reduce the overall value of a bank. (3) Value-added activities that can be separated from non-value added activities are based on the value added assessment. (4) EVA helps the management to set goals in terms of the internal (internal goal setting) so that the destination of bank is based on the long-term implications, not just short term. (5) In the case of EVA investment, it provides a guidance for a project acceptance decision (capital budgeting decision), and in terms of evaluating routine performance (performance assessment) management, EVA helps to achieve value added activities. (6) EVA helps to provide investigation system or provide right incentives (incentive compensation), where the management are encouraged to act as an owner.